Strategy Map Design for Indonesian Ministry of Investment & Downstream Industry 2025-2029 - Rofi, M. Akhsanur; Triananda, Mohammad Ilham (Universitas Prasetiya Mulya, 2025)
The formulation of the National Development Plan (RPJMN) for 2025–2029 and accompanying nomenclature changes marked the start of strategic transformation at the Ministry of Investment and Downstream Industry/Indonesia Investment Coordinating Board (BKPM). Efforts to expand downstreaming were pursued to support an 8% economic growth target over five years. However, surveys evaluating partnership implementation and business-actor feedback indicated that expectations for the partnership process had not been met, hindering MSME inclusion in downstream supply chains. This study aimed to design strategic alignment at BKPM using a strategy-map approach based on RPJMN 2025–2029. It adopted interviews, regulatory and RENSTRA analysis, performance reports, and internal government data. The findings revealed new downstreaming-related strategic objectives, for which indicators were formulated in line with investment and downstreaming theories and visualized in a causal strategy map. This coherence among indicators contributed to achieving strategic objectives and is expected to improve future policy implementation.